Desain Rancang Bangun Trainer Kit untuk Menentukan Pengaruh Jenis Bahan Tali Terhadap Cepat Rambat Gelombang - Linggar Ayu Octaviani; Sri Handono Budi Prastowo; Firdha Kusuma Ayu Anggraeni (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2021)
The aim of the research is to establish the design of the trainer kit project to determine the effect of the rope material type toward the rope wave velocity and the effect of the type of nylon, raffia, polyester, hemp and chinnese satin rope materials on the velocity of rope wave propagation. The research method used is the Research and Development method using Nieveen design. The development of trainer kit uses an Arduino UNO microcontroller equipped with a proximity sensor HC-SR04 for measuring the rope wavelength. One point of the rope is tied with a timer ticker and the other is tied to a hanging load which is resting on a pulley. When the power supply is turned on, the timer ticker will vibrate to move the rope that has been tied. The rope will form a transverse wave. The result of this research, the design of trainer kit is development by using micro-controlled Arduino UNO and a proximity sensor HC-SR04 can be declared as a valid result. There are mass convention impacts of the type of rope likely nylon, polyester, raffia, hemp and chinese satin toward the rope wave velocity.